2018
DOI: 10.1007/s10068-018-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Orostachys malacophyllus var. iwarenge extracts on reactive oxygen species production and lipid accumulation during 3T3-L1 adipocyte differentiation

Abstract: Orostachys malacophyllus var. iwarenge was extracted with water, 30 and 70% ethyl alcohol. The ethyl alcohol extracts showed higher total phenol contents and greater antioxidant effects than the water extract. Treatment with the 70% alcohol extract inhibited reactive oxygen species (ROS) production and lipid accumulation during 3T3-L1 adipogenesis. Furthermore, the 70% extract inhibited the mRNA and protein expressions of the prooxidant enzyme NADPH oxidase 4 and of the NADPHproducing enzyme glucose-6-phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, M. oleifera has been reported to contain mostly quercetin, tocopherols, moringine, kaempferol, glycosides, benzylisothiocyanate, and carotenoids. M. oleifera has been a well‐known resource in drug development programs in the discovery of lead compounds due to novelty in its structure and diverse secondary metabolites (Jang et al, 2019; Vasanth et al, 2015). It is well known that this category of compounds reduces lipid and control glucose level through multiple mechanisms, including adiponectin and insulin sensitivity (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, M. oleifera has been reported to contain mostly quercetin, tocopherols, moringine, kaempferol, glycosides, benzylisothiocyanate, and carotenoids. M. oleifera has been a well‐known resource in drug development programs in the discovery of lead compounds due to novelty in its structure and diverse secondary metabolites (Jang et al, 2019; Vasanth et al, 2015). It is well known that this category of compounds reduces lipid and control glucose level through multiple mechanisms, including adiponectin and insulin sensitivity (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that flavonoids as antioxidants arrested mitotic clonal expansion and inhibited PPARγ, C/EBPα, and aP2 expression (Furukawa et al, 2017;Lee et al, 2009Lee et al, , 2016Lee et al, , 2017. ROS was also reported to upregulate expression of C/EBPα and PPARγ, well-known adipogenic markers (Jang et al, 2019;Lee et al, 2009). cell survival, death, and redox maintenance (Furukawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that flavonoids as antioxidants arrested mitotic clonal expansion and inhibited PPARγ, C/EBPα, and aP2 expression (Furukawa et al, ; Lee et al, , , ). ROS was also reported to upregulate expression of C/EBPα and PPARγ, well‐known adipogenic markers (Jang et al, ; Lee et al, ). Since these C/EBPα and PPARγ promote adipogenesis by inducing expression of adipocyte‐specific genes, including aP2, and overexpression of transcription factors accelerates adipogenesis and lipid accumulation (Csaki & Reue, ; Feve, ; Tanaka, Yoshida, Kishimoto, & Akira, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations